2005
DOI: 10.1121/1.1879212
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of angular and frequency compounding in ultrasonic attenuation estimations

Abstract: Previous reports have shown that the variance in ultrasound attenuation measurements is reduced when spatial and frequency compounding were applied in data acquisition and analysis. This paper investigates factors affecting the efficiency of compound attenuation imaging methods. A theoretical expression is derived that predicts the correlation between attenuation versus frequency slope (beta) estimates as a function of the increment between measurement frequencies (deltaf ) and the angular separation between b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
0
5
0
1
Order By: Relevance
“…A com par i son of the at ten u a tion co ef fi cient es ti mated us ing the di rect fit and power dif fer ence meth ods for all the ex cised plaque spec i mens used in this study are shown in fig ure 8. 24 SHI ET AL…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A com par i son of the at ten u a tion co ef fi cient es ti mated us ing the di rect fit and power dif fer ence meth ods for all the ex cised plaque spec i mens used in this study are shown in fig ure 8. 24 SHI ET AL…”
Section: Methodsmentioning
confidence: 99%
“…22 How ever, for ex-vivo mea sure ments, the ex cised plaque sam ples ob tained af ter ca rotid endarterectomy are usu ally very small, with di men sions of plaque tis sue be ing around 1-2 cm in length and 0.3-0.5 cm thick (plaque thick ness rep re sent tis sue from the in side ar tery wall to the plaque sur face). Sev eral meth ods used to es ti mate the at ten u a tion co ef fi cient described in the lit er a ture 23,24 re quire sam ple thick nesses around 0.5 to 1 cm to pro vide re li able es ti ma tion of the at ten u a tion co ef fi cient. How ever, in our ex-vivo ex per i ments, plaque thickness was usu ally around 0.3 to 0.5 cm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The concept is similar to spatial compounding methods for improving the quality of US B-mode [10], [34]–[36], quantitative US [37], [38] and US strain [11], [39], [40] images. The success of spatial compounding of US images relies on the combination of fully decorrelated speckle patterns, which may be achieved with large relative translations [10] or rotations [41], deformation [26], or variations in transmit parameters, such as frequency [42] and beem steering [43].…”
Section: Introductionmentioning
confidence: 99%
“…Folglich sollten neue sinnenphysiologisch optimierte Farbmappensysteme erarbeitet werden. Fischer et al konnten diese Ansätze der phototopischen Bildgebung bestätigen [18], welche Eingang in die ultraschallkontrastmittelspezifische Bildgebung gefunden haben [20]. Bis zum heutigen Zeitpunkt wurde in den Studien beim Vergleich zwischen Sonografie und Mammografie von bereits entweder mammografisch oder sonografisch detektierten Mikroverkalkungen ausgegangen [2, 3, 5, 6, 12, 21], wobei in den meisten Fällen das Mikrokalkareal gezielt untersucht wurde.…”
unclassified